Effects of Baby Swimming on Motor and Cognitive Development: A Pilot Trial. Issue 4 (August 2022) - Borioni, Federica; Biino, Valentina; Tinagli, Valeria; Pesce, Caterina
Contact with water, even from birth, may be an important experience for child development. In this work, we aimed to investigate if baby swimming might influence infant development in motor and cognitive domains. We assigned infants to either a 10-week baby swimming intervention ( n = 12; M age = 13 months ( SD ) = 7) or a control group ( n = 15; M age = 22 months ( SD ) = 6). We assessed motor development with the Peabody Developmental Motor Scales (2nd edition, PDMS-2) and cognitive development with core tests of executive functions: delayed response for working memory, object retrieval for inhibition, and A-not-B for response shifting. Non-parametric analyses revealed that infants in the baby-swimming group improved in gross, fine, and total motor skills, and showed marginally better inhibition speed and shifting accuracy, with associated gains of shifting accuracy and fine and total motor skills. Even with in this small-sized convenience sample, this pilot study revealed promising benefits from baby swimming on motor development that warrant further study. This preliminary work paves the way for replication and illustrates what effect sizes may be expected in sufficiently powered well-designed follow-up research targeted to aid the joint development of motor and cognitive skills as early as infancy.